Thermal hydraulic performance for hybrid composition ratio of TiO2–SiO2 nanofluids in a tube with wire coil inserts - W. H., Azmi; K., Abdul Hamid; A. I., Ramadhan; A. I. M., Shaiful (Elsevier, 2021)
Hybrid nanofluids flows with wire coils are proven to be beneficial in improving the performance of heat transfer. The thermal-hydraulic performance with different hybrid composition ratio for two or more suspended nanoparticles in the hybrid nanofluids with wire coils is unknown. Therefore, the research work was carried out to evaluate the effect of hybrid composition ratio on the overall system performance for flow with wire coils. The TiO2–SiO2 nanofluids was prepared at constant 1.0% of volume concentration and hybrid composition ratio, R of TiO2 to SiO2 nanoparticles at variation of 0.2, 0.4, 0.5, 0.6, and 0.8. The wire coils were studied for various pitch ratio up to 4.17. The TiO2–SiO2 nanofluids heat transfer was improved up to 211.75% for flow with wire coils. The best thermal performance factor (TPF) was exceeded 1.72 and performed with R = 0.2 composition ratio and pitch ratio of 0.83. The present TPF for hybrid nanofluids is higher than TPF for existing single nanofluids hence confirmed the applicability of TiO2–SiO2 nanofluids at R = 0.2 composition ratio flow with wire coils.